Factors affecting entrepreneurial efforts of ethnic minority women: Case study of the Hmong community in Vietnam - Hoa, Le Anh; Thanh, Nguyen Nghi (Edelweiss Applied Science and Technology, 2024)
The topic explored in this study is the issues related to the entrepreneurial activities of Hmong women in Vietnam, which has been minimally addressed in the literature. A quantitative study design, involving a survey administration to Hmong women involved in entrepreneurial activity, was used to identify the influence of empowerment and personal development, community development and modeling, cultural preservation through entrepreneurship, and economic impact and social change. Evidence from the study indicates that these areas are significant factors explaining motivation and entrepreneurial activities, as well as the role of personal empowerment, community support, cultural integration, and socio-economic context. The conclusion is that entrepreneurship for Hmong women in Vietnam is a contested site and the influence of factors motivating such entrepreneurial activity transcends economic motivations and is situated in personal and cultural development and social engagement relating to socio-economic factors. The findings are important for the development of policies and practices aimed at the support of Hmong women entrepreneurs, and suggest policies and practices should consider social and cultural areas of entrepreneurial activity. Further study should extend this research to a consideration of Indigenous groups and the inquiring of factors motivating entrepreneurial activity through a qualitative study design.